Advanced Tools for Operators at Amazon.com - Bodík, Peter; Fox, Armando; Jordan, Michael I.; Patterson, David; Banerjee, Ajit; Jagannathan, Ramesh; Su, Tina; Tenginakai, Shivaraj; Turner, Ben; Ingalls, Jon (HotAC '06: Hot Topics in Autonomic Computing, 2006)
Despite significant efforts in the field of Autonomic Computing, system operators will still play a critical role in administering Internet services for many years to come. However, very little is know about how system operators work, what tools they use and how we can make them more efficient. In this paper we study the practices of operators in a large-scale Internet service Amazon.com and propose a new set of tools for operators. The first tool lets the operators explore the health of system components and dependencies between them; the other monitors the actions of operators and automatically suggests solutions to recurring problems.